Dopamine and entrepreneurship: Unifying entrepreneur personality traits, psychiatric symptoms, entrepreneurial action and outcomes - Freeman, Michael; Lerner, Daniel; Rauch, Andreas (Elsevier, 2024)
Research conducted over the last three decades confirms that dopaminergic personality traits (Openness, Extraversion and the Industriousness aspect of Conscientiousness) are prominent among entrepreneurs. We highlight the continuum between dopaminergic traits, dimensions, temperaments, symptoms and psychiatric conditions (bipolar spectrum conditions, ADHD, substance and behavioral addictions, and OCPD) among entrepreneurs, and how behavioral manifestations of this continuum affect entrepreneurial action. Despite the pathological potential, the connection with some favorable outcomes of dopaminergic traits and psychiatric conditions suggests that atypical dopamine physiology may be one biomarker of the neurodiversity that distinguishes, empowers and endangers entrepreneurs. By showing the dopaminergic underpinnings of traits, dimensions, symptoms and conditions among entrepreneurs, we offer a unifying framework that contextualizes findings within the construct of dopaminergic differences – a framework that integrates otherwise isolated findings about the personality traits and psychiatric conditions of entrepreneurs. In other words, the neurodiversity biomarkers and bio-psycho-social characteristics found among entrepreneurs often reflect a polygenic endophenotype that features atypical dopamine physiology.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 8 - Trabajo decente y crecimiento económico; entrepreneurship; dopamine; personality; clinical symptoms; psychiatric conditions; psychophysiology; neurodiversity; mental health; bipolar spectrum conditions; ADHD; addiction; OCPD; entrepreneurial action